2019
DOI: 10.1038/s41467-019-13171-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent cationic–aromatic sequences yield strong electrostatic adhesion of hydrogels in seawater

Abstract: Electrostatic interaction is strong but usually diminishes in high ionic-strength environments. Biosystems can use this interaction through adjacent cationic–aromatic amino acids sequence of proteins even in a saline medium. Application of such specific sequence to the development of cationic polymer materials adhesive to negatively charged surfaces in saline environments is challenging due to the difficulty in controlling the copolymer sequences. Here, we discover that copolymers with adjacent cation–aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
239
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(254 citation statements)
references
References 35 publications
2
239
0
Order By: Relevance
“…As indicated in a recent work about mussel-mimic peptide and the ones with Dopa replaced by Tyr and Phe ( 31 ), cation-π interaction occurs in all these three peptides: Lys and aromatic residues tend to form cation-π interactions in the peptides enriched with these two types of residues. Besides, a recent work on the adsorption behavior of copolymer also found that aromatic residues enhance electrostatic interaction of their adjacent cationic residues with the surface ( 67 ). In addition, as a small amount of Dopa or Tyr (~10%) is conjugated to poly-lysine, its adsorption ability is enhanced to a similar extent ( 28 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in a recent work about mussel-mimic peptide and the ones with Dopa replaced by Tyr and Phe ( 31 ), cation-π interaction occurs in all these three peptides: Lys and aromatic residues tend to form cation-π interactions in the peptides enriched with these two types of residues. Besides, a recent work on the adsorption behavior of copolymer also found that aromatic residues enhance electrostatic interaction of their adjacent cationic residues with the surface ( 67 ). In addition, as a small amount of Dopa or Tyr (~10%) is conjugated to poly-lysine, its adsorption ability is enhanced to a similar extent ( 28 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of a lower cross-linking ratio, current tough composite gels have many dangling chains on the surface and show sticky properties 28 30 . In a general hydrogel, in order to exhibit such properties, it is necessary to create an extremely low degree of crosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their three-dimensional porous network, flexibility, and high water content, hydrogels are attractive biomaterial scaffolds for drug delivery, [ 1 , 2 , 3 ] tissue engineering, [ 4 ] vaccines, [ 5 , 6 ] and biosensors [ 7 ]. Several crosslinking strategies including chemical conjugations, [ 8 , 9 ] physical interactions, [ 10 , 11 ] and polymerizations [ 12 , 13 ] have been formulated for hydrogel synthesis. However, the fabrication of next-generation hydrogels with amended functional and structural recapitulations of damaged organs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%